EXTENT OF SATISFACTION WITH THE SERVICES PROVIDED IN UNIVERSITY LIBRARIES FROM THE VIEW POINT OF USERS A CASE STUDY OF AN-NAJAH NATIONAL UNIVERSITY LIBRARIES - Ibrahim Khaleel Khader (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study sought to case the libraries in An-Najah National University in Nablus- Palestine, using the Likert scale (1-5), which contains five variables that reflect the quality of services Provided by the libraries of An-Najah National University for its users. The researcher used the analytical method. results of the study showed that the most expected services in the electronic journals, with a mean value of 4.8, while the least expected service with the ease to access to support books with a mean value 2.0. And the libraries that provide the less services to users were in the agriculture and veterinary medicine library with a mean value 4.5, and the libraries that provide the less services to users were in the Diana Tamari Sabbagh (main library) with a mean value 3.8. The results showed that there were significant differences between the access services to electronic groups with a mean value 4.7% and paperwork by 2.8%. The researcher recommended that more studies need for periodic and continuous to this subject.